A study on issues facing by customers for Celcom broadband in Kuching Sarawak / Sazali Elias - Elias, Sazali (Universiti Teknologi MARA, Sarawak, 2010)
Celcom claims to have the widest and most extensive coverage nationwide among the other mobile operators and also the number one telco in Malaysia. The purpose of this project is to study on issues facing by Celcom Broadband customers in Kuching. There are 1,852 registered Celcom Broadband customers in Kuching of which 200 respondents were completing the questionnaire. In this project paper attention is paid to the measurement for level of satisfaction for Celcom Broadband customers and areas of improvement